The First North American Experience Using Glycosorb Immunoadsorption Columns for Blood Group–Incompatible Kidney Transplantation. (October 2020) - Pavenski, Katerina; Buchholz, Megan; Cheatley, Patti Lou; Krok, Elizabeth; Anderson, Monique; Prasad, GV Ramesh; Qureshi, Mohammed Azfar; Meliton, Galo; Zaltzman, Jeffrey
Background: Blood group incompatibility (ABOi) is the most common barrier to living donor kidney transplantation. Options for such recipients include kidney paired donation (KPD) or desensitization methodology to reduce blood antibody response. Objective: The objective of this study is to report on the first North America experience in ABOi living donor kidney transplantation using Glycosorb ABO immunoadsorption columns. Design: Retrospective observational cohort study. Setting: Renal transplant program at St. Michael's Hospital, Unity Health Toronto, University of Toronto. Patients: Twenty-six ABOi living donor transplants from August 2011 through February 2020 were undertaken at our center. Measurements: Renal allograft and patient survival postdesensitization for ABOi living donor transplants and isohemagglutinin titer reduction. Methods: Preoperative immunosuppressive regimen consisted of a single dose of Rituximab 375 mg/m 2 IV on day −28; tacrolimus, mycophenolic acid, and prednisone to start on day −7. Immunoadsorption treatments with Glycosorb A or B columns were performed on day −7 through day −1 based on anti-A or anti-B titers on Spectra Optia Apheresis System. Immunosuppression included basiliximab, solumedrol followed by oral prednisone, once-daily tacrolimus, and mycophenolic acid. The mean follow-up was 53 months (3-96 months). Results: A total of 26 individuals underwent an attempt at desensitization of whom 24 patients underwent immediate transplant. One patient had a rebound in titers and subsequently was transplanted from a blood group compatible living donor. A second patient had an unrelated medical issue and desensitization was discontinued. Five-year patient survival was 96% and death censored allograft survival was 92%. Posttransplant anti-A or anti-B titers were monitored daily for the first 7 days posttransplant and every 2 days from days 7 to 14. There were no acute rejections seen in this cohort of transplant recipients. Limitations: As our protocol was first initiated as proof of concept, a few recipients had low initial isohemagglutinin titers. This may have contributed to improved clinical outcomes. Conclusions: ABO column immunoadsorption with specific columns is a safe and effective method for ABOi living donor kidney transplantation, and an option when KPD is less than ideal. Trial not registered as this was a retrospective cohort review.